Establishment of Carotid Artery Dissection and MRI Findings in a Swine Model - Peng, Jing; Wu, Min; Doycheva, Desislava Met; He, Yi; Huang, Qiongzhen; Chen, Wei; Matei, Nathanael; Ding, Jun; Chen, Kangning; Xu, Ningbo; Zhou, Zhenhua (Frontiers in Neurology, 2021)
Carotid artery dissection (CAD) is the leading cause of ischemic stroke in young patients. However, the etiology and pathophysiology of CAD is unknown. In our study, two types of dissections (length × width: 1.5cm × 1/3 circumference of intima; Group I, n=6 or 1.5cm × 2/3 circumference of intima; Group II, n=6) were created between the media and intima. Ultrasound (within 2hours after dissection) showed a dissociated intima in the lumen and obstructed blood flow in the surgical area in all. Digital Subtraction Angiography (DSA, 72hours after dissection), Magnetic Resonance Imaging (MRI, 72hours after dissection) and Hematoxylin-eosin (H&E, 7day after dissection) staining demonstrated stenosis (33.67 ± 5.66%) in Group I and total occlusion in Group II. In conclusion, a CAD model is successfully established in swine with detacher and balloon dilation under microscope in ten out of twelve swine and the morphological changes (stenosis or occlusion) after CAD were determined by the size of intimal incision.